Constraining the shape of dark matter haloes with globular clusters and diffuse stellar light in the E-MOSAICS simulations. Issue 4 (28th March 2023) - Reina-Campos, Marta; Trujillo-Gomez, Sebastian; Pfeffer, Joel L; Sills, Alison; Deason, Alis J; Crain, Robert A; Kruijssen, J M Diederik
ABSTRACT: We explore how diffuse stellar light and globular clusters (GCs) can be used to trace the matter distribution of their host halo using an observational methodology. For this, we use 117 simulated dark matter (DM) haloes from the $(34.4~\rm cMpc)^3$ periodic volume of the E-MOSAICS project. For each halo, we compare the stellar surface brightness and GC projected number density maps to the surface density of DM. We find that the dominant structures identified in the stellar light and GCs correspond closely with those from the DM. Our method is unaffected by the presence of satellites and its precision improves with fainter GC samples. We recover tight relations between the dimensionless profiles of stellar-to-DM surface density and GC-to-DM surface density, suggesting that the profile of DM can be accurately recovered from the stars and GCs (σ ≤ 0.5 dex). We quantify the projected morphology of DM, stars, and GCs and find that the stars and GCs are more flattened than the DM. Additionally, the semimajor axes of the distribution of stars and GCs are typically misaligned by ∼10 degrees from that of DM. We demonstrate that deep imaging of diffuse stellar light and GCs can place constraints on the shape, profile, and orientation of their host halo. These results extend down to haloes with central galaxies M ⋆ ≥ 10 10  M⊙, and the analysis will be applicable to future data from the Euclid,   Roman, and the Rubin observatories